Revisiting front-of-pack nutrition labeling policies in Indonesia - Muhammad Nidhal; Ibnu Budiman (Center for Indonesian Policy Studies (CIPS), 2025)
Effective implementation of Government Regulation (GR) No. 28/2024 on addressing excessive sugar, salt, and fats (SSF) consumption requires robust front-of-pack nutrition labeling (FoPNL) technical guidelines that prioritize public health while incorporating phased implementation. Interpretive warning labels are suggested as these have been proven effective from a public health perspective in middle-income countries like Chile, Mexico, Peru, and Uruguay. The FoPNL technical guidelines should also consider advancing a co-regulatory approach when transitioning to a mandatory scheme, enhancing consumer nutritional literacy, and strengthening the governance arrangements among key food regulators.
Keywords: 330